1989
DOI: 10.2166/wst.1989.0071
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Toxins in Water

Abstract: Cyanobacteria (blue-green algae) commonly occur in fresh- and brackish waters and may produce massive annual growths as a consequence of nutrient enrichment from natural waters, agricultural fertilizer run-off, or from domestic/industrial effluents. The cyanobacterial species which dominate these growths typically belong to the genera which produce toxins. Cyanobacterial toxins cause fatal poisonings of agricultural livestock, wild animals, birds and fish on a world-wide basis. The involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(92 citation statements)
references
References 0 publications
1
85
0
6
Order By: Relevance
“…Laboratory studies have shown that the toxicity (LD 50 , mg dry algae kg À1 mice) of temperate strains of M. aeruginosa were highest at 18-20 C, and decreased greatly as the temperature increased above 28 C (van der Westhuizen and Eloff, 1985;Watanabe and Oishi, 1985). Culture-based studies have shown that MC concentrations are generally highest between 20 and 25 C (van der Westhuizen and Eloff, 1985;van der Westhuizen et al, 1986;Codd and Poon, 1988;Amé and Wunderlin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have shown that the toxicity (LD 50 , mg dry algae kg À1 mice) of temperate strains of M. aeruginosa were highest at 18-20 C, and decreased greatly as the temperature increased above 28 C (van der Westhuizen and Eloff, 1985;Watanabe and Oishi, 1985). Culture-based studies have shown that MC concentrations are generally highest between 20 and 25 C (van der Westhuizen and Eloff, 1985;van der Westhuizen et al, 1986;Codd and Poon, 1988;Amé and Wunderlin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Toutefois, ces techniques classiques ne permettent pas une élimination totale des microorganismes pathogènes ; d'où la nécessité de soumettre l'eau à une autre technique de désinfection. En outre, parmi les inconvénients de ces techniques, il faut noter la production de boues, comme dans le cas de procédés de coagulation-floculation, ou de produits indésirables, comme dans le cas de certains procédés de désinfection, telle que la chloration (Godd et al, 1989).…”
Section: Introductionunclassified
“…Under favorable nutritional and environmental conditions, they proliferate into cyanobacterial blooms, which are becoming more common with the increasing eutrophication of fresh water bodies. The concern over the outcome of cyanobacterial blooms has increased during the past decades with increasing information on the detrimental power of the toxins produced by these organisms [1][2][3]. They are known to be a rich source of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%